Risk Factors for Tuberculosis Among Livestock Farmers in Geyer and Toroh Districts, Grobogan Regency - Aisyah Purnomosari; Martini Martini (Jurnal Epidemiologi Kesehatan Komunitas, 2026)
Background: Tuberculosis (TB) remains a major global public health problem. The World Health Organization (WHO) estimated 10.8 million new TB cases and 1.2 million deaths worldwide in 2023. Indonesia is among the countries with the highest TB burden. Livestock farmers may face additional occupational exposure risks due to prolonged exposure to enclosed barn environments characterized by high humidity, organic dust, ammonia accumulation, and limited ventilation. However, evidence regarding TB risk factors in livestock farming communities remains limited.Methods: A retrospective case–control study was conducted among 156 livestock farmers in Geyer and Toroh Districts, Grobogan Regency (78 TB cases and 78 controls matched by village). Cases were individuals aged ≥18 years with confirmed TB diagnoses documented in medical records. Controls were farmers without TB history from the same communities. Data were collected using structured interviews and environmental observation checklists. Associations were examined using chi-square tests and multivariable logistic regression, with adjusted odds ratios (AORs) and 95% confidence intervals (CIs).Results: Eight variables were associated with TB in bivariate analysis. After adjustment, age remained the only independent predictor. Farmers aged >50 years demonstrated a 3.6-fold higher likelihood of TB compared with younger farmers (AOR=3.612; 95% CI: 1.689–7.684). The final model accounted for 23.6% of variance (Nagelkerke R²=0.236).Conclusion: Age >50 years is the dominant risk factor for TB among livestock farmers. Targeted TB screening and occupational health integration are urgently needed in rural farming communities